Combined Computational and Experimental Studies of Anabasine Encapsulation by Beta-Cyclodextrin - Muldakhmetov, Z.; Fazylov, S.; Nurkenov, O.; Gazaliev, A.; Sarsenbekova, A.; Pustolaikina, I.; Nurmaganbetov, Zh.; Seilkhanov, O.; Alsfouk, A.A.; Elkaeed, E.B.; Eissa, I.H.; Metwaly, A.M. (Plants, 2022)
The encapsulation of the famous alkaloid, anabasine, with -CD was studied to obtain a more stable and bioavailable inclusion complex. Various in silico and experimental studies of the obtained -CD-anabasine complex are presented. Firstly, molecular docking studies were conducted against the , , and cyclodextrins to explore which subclass is the best for encapsulation. The obtained results that pointed at -cyclodextrin were further confirmed by five MD simulations and MM-PBSA studies. Experimentally, the spectral properties of the anabasine -cyclodextrin complex were determined by FT-IR, 1H, and 13C-NMR spectroscopic methods. Additionally, the surface morphology of the anabasine -cyclodextrin was investigated using a scanning electron microscope. Furthermore, the outputs of the thermographic measurements utilizing a differential scanning calorimeter were displayed. The activation energy of the reaction of thermo-oxidative destruction of the clathrate complex was calculated, and the kinetic parameters of the thermal destruction processes were decided using the Freeman–Carroll, Sharpe–Wentworth, Achar, and Coates–Redfern methods. The kinetic parameters of the thermal decomposition of the anabasine -cyclodextrin were in agreement and verified the reliability of the obtained results. The obtained computational, spectral, morphological, and thermogravimetric results verified the successful formation of the anabasine -cyclodextrin complex.
Keywords: inclusion complex; clathrate; b -cyclodextrin; anabasine; substrate; thermal decomposition of -cyclodextrin